1992
DOI: 10.1182/blood.v79.11.3067.bloodjournal79113067
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation for Philadelphia chromosome-positive acute lymphoblastic leukemia

Abstract: Philadelphia chromosome (Ph1)-positive acute lymphoblastic leukemia (ALL) has a poor prognosis when treated with conventional chemotherapy. We analyzed the outcome of 67 HLA-identical sibling bone marrow transplants (BMTs) for Ph1-positive ALL reported to the International Bone Marrow Transplant Registry (IBMTR). Twenty-one of 67 (31%) transplant recipients survived in continuous complete remission more than 2 years after transplant. Two-year actuarial probabilities (95% confidence interval) of leukemia-free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…Furthermore, despite improvements in CR rates for Ph-positive ALL with newer treatments, alloSCT still is considered the mainstay of treatment for this patient subgroup. 16 However, this notion is being challenged. Several factors influence the outcome of patients who undergo alloSCT.…”
Section: Standard Chemotherapy and Allogeneic Stem Cell Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, despite improvements in CR rates for Ph-positive ALL with newer treatments, alloSCT still is considered the mainstay of treatment for this patient subgroup. 16 However, this notion is being challenged. Several factors influence the outcome of patients who undergo alloSCT.…”
Section: Standard Chemotherapy and Allogeneic Stem Cell Transplantationmentioning
confidence: 99%
“…5,[8][9][10][11][12][13][14] Patients with Ph-positive ALL who received conventional chemotherapy reportedly had long-term survival rates of approximately 10%, 5,12,14 and only allogeneic stem cell transplantation (alloSCT) extended long-term survival in 38% to 65% of patients. [15][16][17][18][19][20][21] Outcomes for patients with Ph-positive ALL improved substantially with the introduction of the tyrosine kinase inhibitor (TKI) imatinib mesylate. Although imatinib monotherapy in previously treated patients with Ph-positive ALL produced only a modest, short-lived response, 22,23 imatinib combined with chemotherapeutic regimens has induced complete remissions (CRs) in almost every patient ($95%) with newly diagnosed Ph-positive ALL.…”
mentioning
confidence: 99%
“…More aggressive therapy protocols such as myeloablative chemotherapy with bone marrow transplantation (BMT) as consolidation of ®rst CR are the treatment of choice in younger patients. However, even with aggressive treatment recurrence of the disease is still a major problem and the probability of relapse (40±80%) is high (Barrett et al, 1992;Miyamura et al, 1992;Forman et al, 1987). The situation in patients receiving transplants in relapse is even worse Chao et al, (Clark et al, 1988;Schaefer-Rego et al, 1988;Hermans et al, 1987).…”
mentioning
confidence: 99%
“…There have been several reports regarding stem cell transplantation, but the outcome of the patients was variable. Some investigators reported relatively good results [13,14] whereas the others did not ®nd much bene®t in this treatment strategy [15,16]. One of the reasons for this discrepancy was that there are very few reports describing the outcome of a large series of patients.…”
Section: Discussionmentioning
confidence: 99%